The major species group of the genus Geodromicus L. Redtenbacher, 1857 (Coleoptera, Staphylinidae, Omaliinae, Anthophagini), and additional faunistic data on some Palaearctic species - Shavrin, Alexey V. (Zootaxa, 2026)
The monotypic major species group of the genus Geodromicus Redtenbacher, 1857, consisting of G. major Motschulsky, 1860 (Crimea, Caucasus, Turkey), is reviewed. The following new synonymies are established: G. major = G. anatolicus Fagel, 1976 syn. nov., = G. dubiosus Fagel, 1976 syn. nov., = G. laticollis Fagel, 1976 syn. nov., = G. svaneticus Iablokoff-Khnzorian, 1989 syn. nov. The following synonymies previously established by Iablokoff-Khnzorian (1989) are confirmed: G. major = G. asiaticus Bernhauer, 1902, = G. gracilicornis Luze, 1903, = G. languidus Luze, 1903, = G. striatus Khnzorian, 1962, = G. ponticus Fagel, 1976, = G. caucasianus A. Bordoni, 1984, = G. luzianus A. Bordoni, 1984. Lectotypes are designated for G. gracilicornis and G. languidus. A distribution map for G. major is provided. Additionally, faunistic records of nine Palaearctic species of Geodromicus are provided. Several species are recorded from a certain area for the first time: G. anlasi Shavrin, 2021 from Bolu, Erzurum and Ardahan (Turkey), G. bodemeyeri Bernhauer, 1902 from Sinop and Ordu (Turkey), G. brevicollis Fauvel, 1875 from Kars (Turkey), G. major from Crimea (Ukraine), Stavropol Area and Chechen Republic (Russia), and Trabzon, Rize, Gümüşane, Artvin, Kars, Erzurum, Malatya and Adiyaman (Turkey), G. plagiatus (Fabricius, 1798) from Albania, and G. zwickianus Fagel, 1976 from Erzurum and Kars (Turkey).